Perangkat Lunak Mobile Trivia Game Untuk Membantu Meningkatkan Hafalan Dan Wawasan Anak Anak Terhadap Surah Pendek Al Quran - Listiananda Apriliawan; Afriyudi Afriyudi; Siti Sauda (Journal of Information Technology Ampera, 2020)
The development of mobile trivia game software is motivated by the tendency of children over the age of 7 who prefer digital devices and are better able to utilize the information presented by games. The mobile trivia game software is expected to be a solution that can meet the needs of children aged over 7 years starting from the aspect of education which is very important to be a shared concern for all elements in the society. The development of the software system can be realized by using the Extreme Programming method which modeling can use a CRC card. The work is done in a very short time. The results of the implementation of the development of mobile trivia game software can provide benefits to children aged over 7 years, especially to help improve their memorization and insight into the Qur'an's Juz Amma. As has become the hope for the author, namely creating educational software for children over 7 years